Outcome of Patients With Metastatic Lung Neuroendocrine Tumors Submitted to First Line Monotherapy With Somatostatin Analogs - Lenotti, Elisa; Alberti, Andrea; Spada, Francesca; Amoroso, Vito; Maisonneuve, Patrick; Grisanti, Salvatore; Baggi, Alice; Bianchi, Susanna; Fazio, Nicola; Berruti, Alfredo (Frontiers in Endocrinology, 2021)
Objective Antiproliferative activity of somatostatin analogs (SSAs) has been demonstrated in digestive neuroendocrine tumors (NETs), but few data have been published in patients with pulmonary NETs. We therefore conducted a retrospective study to provide additional data on the outcome of patients with metastatic lung NETs submitted to front line SSAs. Research Design and Methods Patients with metastatic lung NET treated with first line SSA-monotherapy (octreotide or lanreotide) in two different reference Institutions were reviewed. Outcome measures were progression-free survival (PFS) overall survival (OS), overall response rate and safety. We also explored prognostic factors associated with PFS. Methods The outcome of consecutive patients (pts) with metastatic lung NETs, who underwent first-line treatment with SSAs, recruited from 2014 on 2019 in two Italian reference Institutions, was retrospectively evaluated. Results Thirty-one patients entered the study: 14 (45.2%) with typical and 17 (54.8%) atypical carcinoid. Six patients (19.4%) had a carcinoid syndrome. 60.0% of patients had Ki-67 ≤ 10%. Two (6.5%) patients obtained a partial response, 24 (77.4%) disease stabilization while 5 (16.1%) had progressive disease. Median progression free survival (PFS) was 28.6 months, median overall survival (OS) was not attained. Ki-67 ≤ 10%, typical carcinoid histotype and non-functioning disease, were associated with a non-significant PFS prolongation. PFS in patients with atypical carcinoids and in those with Ki-67 >10% was greater than 19 months. Conclusions The long PFS and OS obtained in this case series suggest that SSAs could be effective as first line approach in the management of patients with progressive, metastatic pulmonary NET.